Bear (Seven Stories Press, 2023)
"Bear, Staffan Gnosspelius's debut book, is a gorgeous visual meditation on depression. In this deeply affecting, wordless picture book for adults, a bear is maddeningly afflicted with a cone that covers his head and that he is unable to take off. He furiously stomps and yells and tears at the cone, he implores the skies and fate for relief, he is drawn to dark and wild and scary places. The depths of his sadness feel like a defeat. It's a battle he wages until he's mentally and physically exhausted. Then, one day, Bear hears notes of music, the humming of a friendly hare. The hare hovers nearby, concerned, sometimes driven away by Bear's frustration and anger, more often staying close and gently offering support. The author began drawing a bear with a cone on his head as a way to make sense of how a person close to him was suffering from mental illness. The resulting book is both an emotional gut punch and a warm embrace, recognizable immediately to anyone who has ever suffered or loved someone who has suffered in similar dark places. In other words, all of us."--